Systematic Literature Review on Multivariate Analysis: Research Trends, Methods and Frameworks - Zuhra, Fatimah (Fakultas Pertanian, 2025)
The focus of this research is to look at the development of analytical multivariate statistical research from 2000-2025. This study tries to identify fundamentally and thoroughly which journal-related multivariate analysis developments are the most significant, the most influential researchers, what research topics are developing, the types of datasets and methods used in multivariate analysis. Bibliometric analysis is used to look systematically based on relevant information from scientific publications, multivariate analysis articles accessed through IEEE Explore and Scopus. In the bibliometric analysis stage using Vosviewer, as many as 483 journals were analyzed for the number of citations, analysis of interconnected keywords and others. Therefore, it was found that the most significant journals were IEEE Transactions on Biomedical Engineering, IEEE Transactions on Geoscience and Remote Sensing. The most influential authors are B. Aiazzi; S. Baronti; M. Selva; with a total of 643 citations writing about the regression multivariate adopted to improve spectral quality. Emerging Research Topics Multivariate Time Series Forecasting. Methods that often appear are Regression, Correlations, Clustering, Principle Component Analysis.